2004
DOI: 10.1038/sj.mp.4001614
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the RELN gene as a genetic risk factor for autism

Abstract: Several genome-wide screens have indicated the presence of an autism susceptibility locus within the distal long arm of chromosome 7 (7q). Mapping at 7q22 within this region is the candidate gene reelin (RELN). RELN encodes a signaling protein that plays a pivotal role in the migration of several neuronal cell types and in the development of neural connections. Given these neurodevelopmental functions, recent reports that RELN influences genetic risk for autism are of significant interest. The total data set c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
1
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 48 publications
9
113
1
5
Order By: Relevance
“…[179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD. However, in another study, 178 the most common repeat 10 was over-represented in AD. One study 177 reported an association of the more common allele of SNP rs736707, which has not yet been replicated by other studies and might not be of functional relevance, as it is located in intron 59 of RELN.…”
Section: Chromosomementioning
confidence: 84%
See 1 more Smart Citation
“…[179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD. However, in another study, 178 the most common repeat 10 was over-represented in AD. One study 177 reported an association of the more common allele of SNP rs736707, which has not yet been replicated by other studies and might not be of functional relevance, as it is located in intron 59 of RELN.…”
Section: Chromosomementioning
confidence: 84%
“…The most commonly assessed variant in RELN is a trinucleotide repeat polymorphism in the 5 0 UTR with unknown functional relevance. Three studies did find an association, [176][177][178] five other studies of comparable size and power did not find an association of the 5 0 UTR trinucleotide or other variants with AD. [179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD.…”
Section: Chromosomementioning
confidence: 85%
“…region before the start codon, have reached conflicting results. [43][44][45][46][47][48][49] This may reflect only the common pattern of nonreplication of early claims from small studies 50 or a modest effect may still be present. A large study should be conducted on this association.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of other immunerelated genes have been implicated in ASD, including macrophage migration inhibitory factor (MIF), 43 MET encoding tyrosine kinase, 44 the serine and threonine kinase C gene PRKCB (alias PRKCB1), 45 protein phosphatase and tensin homolog (PTEN), 46 and the reelin gene (RELN). [47][48][49] It is not known whether immune activation plays an initiating or ongoing role in the pathology of ASD. Immune activation leading to inflammation can have serious detrimental effects and could lead to destruction of tissues.…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%